PREDICTING AUDIT DELAY OF CONSUMER GOODS COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Rif'at, Akhmad; Sulistyowati, Wiwit Apit (EAJ (Economic and Accounting Journal), 2019)
The audit delay is the length of time the completion of the audit performed by the independent auditor as measured from the date the company books close to the date of signing of the independent auditors on audit reports. This research aims to analyze the influence of profitability, solvability, and the solvability partially against the audit delay on the company's industrial sector manufacturing consumer goods listed on the Indonesia stock exchange for the period 2014 up to 2016. The selection of the sample in this research was done using a purposive sampling method and acquired 32 companies as samples. The data used are of audited financial reporting of the sample companies published through the site www.idx.co.id and the official website of each company. Data analysis method used in this research is by using multiple linear regression. Before using regression analysis, then performed a classic assumption test first, which includes a test of normality, multicollinearity test, autocorrelation test, and test heteroskedasticity. Testing in this study performed using SPSS software version 23 for windows. The results of this research show that partially profitability, solvability, and the solvability have no effect against the audit delay.